Development of Microactuators Based on the Magnetic Shape Memory Effect - Yeduru, Srinivasa Reddy (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2013)
The giant magneto-strain effect in Ni-Mn-Ga alloys is particularly attractive for actuator applications. Two different approaches are being pursued to develop MSM microactuators. To observe large deflections of Ni-Mn-Ga microactuators, the material should be exhibiting low twinning stress and large magnetic anisotropy. In addition, design rules and boundary conditions for operating the Ni-Mn-Ga actuator material are having significant importance for evolution of performance characteristics.